Ecological Study of Epiphytic Algae on Aquatic plants Ceratophyllumdemersumand Imperatacylindricain East Euphrates Drainge /(AL-Hefar)AL-Dawaniya/Iraq - Alkam, Foad M.; AL- Khazali, Zahrah K. (Al-Qadisiyah Journal of Pure Science, 2017)
The current investigate included study some physical and chemical properties and epiphytic algae in East Euphrates Drainage(AL-Hefar) were studied during the period from November 2012 till April 2013 Three Sites were chosen along TheDrainage,Twomacrophytes are frequently found,Ceratophyllumdemersumand Imperatacylindrica. these macrophytes are chosen to study epiphytic algae .The Results showed that water of the Drainage was alkaline, very hard ,and well oxygenated. Identification of epiphytic algae reached to(249) species, the Bacillariophyceae ( diatoms ) were dominant with(153) species about(61.4%) followed by Chlorophyceae with (47) species about(18.9%) , and (38) species about (15.3%) related to Cyanophyceaeand (9) species about(3.7%) related to Euglenophyceae .and (2) species about (0.8%) related toDinophyceae. In addition , epiphytic algae on Ceratophyllumdemersumwas higher , than Imperatacylindrica study area . Also , the study showed dominancy of Bacillariophyceae species like Gomphonema ,Cymbella,,Cocconies , Nitzschia, Ahnanthes ,Navicula.